PERANAN TAX AVOIDANCE, INVESTMENT OPPORTUNITY SET, DAN MANAJEMEN ASET TERHADAP NILAI PERUSAHAAN (Studi Kasus Pada Perusahaan LQ45 yang Terdaftar di Bursa Efek Indonesia Periode 2019-2020): (Studi Kasus pada Perusahaan LQ45 yang Terdaftar di Bursa Efek Indonesia Periode 2019-2020) - Enny Prayogo; Rini Handayani; Jeanifer Cornelia Clara (Universitas Pendidikan Ganesha, 2022)
The purpose of the study is to analyze the impact of tax avoidance, investment opportunities set, and asset management on the value of the company. The study population used stocks registered in the LQ45 index in 2019 and 2020. The samples in this research consisted of 30 companies whose sampling techniques used purposive sampling. Hypothesis tests use multiple regression analysis by running F-tests and T-tests. The results of this study conclude that there is a simultaneous influence of tax avoidance, investment opportunity set and asset management on the value of the company by 80.8%. Partly, tax avoidance variables have no effect on the value of the company, while investment opportunity set variables and asset management affect the value of the company.